PENGARUH PEMBERIAN EKSTRAK BIJI KLABET (Trigonella foenum-graecum L.) TERHADAP PERKEMBANGAN UTERUS TIKUS PUTIH BETINA GALUR WISTAR PREPUBERTAL - agustini, kurnia; Wiryowidagdo, Sumali; Kusmana, Dadang (Jurnal Sains dan Teknologi Indonesia, 2007)
Phytoestrogen is the chemical compound contains in plant which has estrogenic like effect. Estrogen has important function on woman’s sexual organ, such as proliferation of uterine and vaginal cornification. Phytoestrogen are weak agonists for estrogen and illicit statistic significantly increases in uterine wet weight, at definite dose, in uterothrophic bioassay. Biji Klabet or Fenugreek (Trigonella foenum-graecum L.) contains steroidal sapogenins such as diosgenin, tigogenin, gitogenin, yamogenin and trigoneoside, that suspected having an estrogen-likeeffect or as phytoestrogen. The aim of this research was to investigate the estrogenic effect of fenugreek’s ethanolic extract in immature rat models. These models represent the climacteric/menopause phase, where estrogen level is verylow because ovary produces no estrogen. The testing animals were divided into five groups, namely normal group, estradiol control group and three level doses of fenugreek extract (30mg/200gBW; 60mg/200gBW and 120mg/200gBW). Theresult indicated that on 120mg/200gBW, fenugreek extract significantly (=0.05) increasing wet weight uterine and proliferation of uterine, such as uterine thickness and uterine diameters. Fenugreek extract, start on 60mg/200gBW, also induces vaginal lubrication and estrus cycle.